Enhancing Community Awareness Through Waste Bin Provision at Pangkalan Bunut Market to Achieve a Clean and Healthy Environment - Legawati, Lisa; Yolanda, Yogi; Meldha, Zuqni; Sembiring, Maria Peratenta; Zulfansyah, Zulfansyah; Ermal, Dini Aulia Sari (Journal of Social and Community Service, 2025)
Environmental awareness and concern for cleanliness remain common challenges, not only in urban areas but also in rural communities. In Pangkalan Bunut Village, the issue of poor waste management persists, largely due to limited community awareness and the lack of adequate waste disposal facilities. To address this problem, our Community Service Team implemented a program to provide waste bins in the Pangkalan Bunut Market. This initiative aimed to encourage proper waste disposal practices, improve environmental awareness, and promote a clean and healthy environment. The program produced several positive outcomes: (1) increasing community understanding of the importance of waste management and environmental care; (2) providing accessible waste bins at the market to support cleaner surroundings; and (3) fostering behavioral change, as residents became more aware of the importance of proper waste disposal. This initiative is expected to serve as a model for sustaining cleanliness and environmental health in Pangkalan Bunut Village.